Priming of pumpkin seeds with salicylic acid in response to salt stress - Martins de Santana, Douglas; Diego Borges de Sousa; Fábio Oliveira Diniz (Comunicata Scientiae, 2025)
Salicylic acid is a phenolic hormone that influences the physiological and biochemical processes of plants, including resistance to biotic and abiotic stresses like salinity. The aim of this study was to evaluate the priming of pumpkin seeds with salicylic acid to mitigate salt stress during germination and early development. An entirely randomized design was used, in a 4 × 4 factorial scheme, using different doses of the phytohormone (100, 150, and 200 mg L−1 and distilled water) and salinity levels (0, 2, 4, and 6 dS m−1), with four replicates. Two genotypes, hybrid cv. Atlas and creole variety were used. The priming period of the seeds in salicylic acid was 8 hours. Then, the seeds were packed in germitest paper, soaked in saline solution, and placed in a germinating chamber. The initial germination count, germination percentage, and abnormal seedlings were evaluated. In a greenhouse, the emergence test was conducted with the seeds primed seeds. Saline solution was provided once a day. The percentage of emergence, emergence speed index, shoot and root length, and shoot and root dry mass were evaluated. The salt stress compromised seed germination and seedling development. The hybrid was sensitive to the salinity of 2 dS m−1, while the creole variety tolerated salinity up to 2 dS m−1. Priming of pumpkin seedlings with salicylic acid did not relieve salt stress during germination and early development.